PENGARUH MOTIVASI BELAJAR, CARA BELAJAR DAN PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS ICT TERHADAP HASIL BELAJAR - Yulia Valentina; Teddy Rusman; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
This study aimed to determine the effect of motivation to learn, how to learn, and use of ICT-based instructional media on the results of class X students studying Economics semester 4 Metro State High School Academic Year 2012/2013. The results (1).There is a positive and significant influence learning motivation the results of Class X students studying Economics Odd Semester 4 Metro State High School Academic Year 2012/2013. (2).There is a positive and significant influence on How to Learn Student Learning Outcomes Economy Class X Odd Semester 4 Metro State High School Academic Year 2012/2013. (3).There is a positive and significant utilization ICT-Based Learning Media for Students Learning Outcomes Economy Class X Odd Semester 4 Metro State High School Academic Year 2012/2013. (4).There is a negative influence motivation to learn, How to Learn, and Use of ICT-Based instructional media the results of Class X students studying Economics Odd Semester 4 Metro State High School Academic Year 2012/2013.Keyword: Learning Motivation, How to Learn, Use of Media ICT-Based Learning, and Learning Outcomes